The contribution of public health medicine specialists to South Africa's health system - Zweigenthal, Virginia E M (Department of Public Health and Family Medicine, 2017)
Background: While South Africa's Constitution, health legislation and policies value public health (PH) approaches, Public Health Medicine (PHM) specialists are largely invisible in the health services. Despite this, many undertake specialist training. The reasons for this mismatch, for doctors' motivations for this training, and the career paths of PHM specialists are not known – nor is it known if their practice is aligned with the intentions of trainers, policy makers and employers. Postulates for their invisibility are that they are not required, are unknown, are interchangeable, not 'service-ready' or unavailable. Aims: This thesis investigates the match between 'desired', 'actual' and 'intended' use of doctors with PH expertise in contemporary South Africa. It explores the motivations of doctors undertaking PH studies, the actual careers of PHM specialists and the intended roles of this cadre of staff. Methods: Firstly, through an electronic survey, motivations for studying and career paths of doctors completing Master of Public Health (MPH) at the University of Cape Town – the foundational PH training for selected specialist training – were examined. Secondly, through focus groups and in-depth interviews, motivations for specialist training, anticipated career paths and perspectives of the future of PHM and of specialists-intraining (registrars), were probed. An on-line survey of PHM specialists' career paths, their reflections on the speciality's value and future was undertaken. Finally, through in-depth interviews, a qualitative study explored the perspectives of key stakeholders in South Africa's health service about PHM's value in the context of current health system reform. Findings: A number of factors underlie PHM's absence in the services. In post-apartheid South Africa, PH functions have been overshadowed by an inordinate focus on 'personal' curative services. Under current legislation, PHM is largely not a requirement for service positions, resulting in many participants (20%) not registering as specialists. PH practice is context-specific and its core functions are practised by others, resulting in overlapping boundaries between PHM and other trained professionals. Together with poor advocacy for the speciality, these resulted in PHM largely being eclipsed in health system design. In 2010, PHM comprised less than 200 specialists, mainly mature doctors who are increasingly female. There was a close match between 'desired', 'actual' and 'intended' roles of PHM specialists. Unlike doctors who undertook MPH studies to obtain research and technical skills, together with population approaches for career progression, PHM registrars and specialists trained to impact on health systems, underpinned by a commitment to social justice. Specialists' broad theoretical and experiential training produced versatile professionals able to work in complex service settings, with competencies spanning strategic and technical functions, which fast-tracked them for leadership. In 2010, a third of PHM specialists worked for the state health sector and a third for universities, mostly as managers or academics; the rest in NGOs, research institutions or independently. Besides those in 'joint appointment' health service and academic posts, less than a handful worked in designated service specialist posts. Specialists were highly satisfied with their careers. The majority had worked in the state sector at one time, but many had left to pursue academic and other careers. Although salaried specialists' remuneration had improved following the Occupational Specific Dispensation (OSD), this had not affected those in management and would not attract prospective specialists to management positions unless the work environment favouring autonomy and innovation improved. Despite an uneven presence, study participants agreed that the PHM's contribution centred on a 'public health intelligence' function – finding and interpreting information; supporting services through management and leadership; providing policy making and planning capacity and research at various levels. Some argued for PHM to be a requirement for senior line management posts in the future. Conclusions and recommendations: South Africa's current health reform is an opportunity for PHM to refine its professional identity, competencies and location. Being cognisant of its multi-disciplinary nature, it must locate itself in a common identity of a profession and workforce, in "a fabric of many professions dedicated to a common endeavour".10 A 'public health identity' needs to be constructed, reflecting the diverse PH professional functions.11 The desired size, shape and roles of the PH workforce, including PHM specialists, needs to be addressed through fora of PH stakeholders – the governmental health sector, civil society employers, universities, existing and prospective specialists - focussing on positions for specialists and PH professionals, the creation of posts, the design of training curricula, and registrar placements. Research that evaluates and explores the development of the PH workforce in South Africa, comparing it with other country settings, will inform the development and competency of the profession, and the health sector that aims to "improve quality of life for all".